Early electrophysiological basis of experience-associated holistic processing of Chinese characters. - Hui Chen (Public Library of Science (PLoS), 2013)
Recent studies have found holistic processing to be a marker of expertise for perception of words in alphabetic (e.g., English) and non-alphabetic (e.g., Chinese) writing systems, consistent with what has been found for faces and other objects of face-like expertise. It is unknown, however, whether holistic processing of words occurs in an early, perceptual stage as it does for faces. We examined how early holistic processing of Chinese characters emerges by recording the event-related potentials (ERPs) in an adaptation paradigm. Participants judged if the top parts of two sequentially presented characters were the same or different while ignoring the bottom part. An early potential (P1) at the posterior channels was smaller when the attended top parts were the same compared with when they are different, indicating an adaptation effect. Critically, for trials with identical top parts, P1 was larger when the irrelevant bottom parts were different, indicating a release of adaptation. This effect was present only when the two character parts were aligned but not misaligned, and only for characters but not for pseudocharacters. The finding of early sensitivity to all parts of a Chinese character suggests that Chinese characters are represented holistically at a perceptual level.